Pemanfaatan Website untuk Selekta Galaktika Musik sebagai Sarana Meningkatkan Promosi Usaha di Masa Pandemi Covid-19 - Hendra Kurniawan (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The COVID-19 pandemic in Indonesia has had a major impact on the economic sector. Many business actors (Micro, Small, and Medium Enterprises) are experiencing a decrease in turnover and income, as well as an increase in debt. Some of the business constraints faced by business actors today include marketing, debt payments, payment of employee wages, rental payments, and raw material costs. The biggest obstacle lies in the marketing or sales of products with a percentage of 48.60%. This condition is also felt by Selekta Galaktika Musik which is a business actor engaged in the sale of special musical instruments for guitars, which is located at Jl. Janti 37A Caturtunggal, Depok, Sleman, D.I. Yogyakarta. The guitar products marketed come from local craftsmen in the village area of ??Bregan, Baki, Sukoharjo, Central Java. The COVID-19 pandemic that has occurred to date and the entry of imported products through the marketplace platform has had a major impact on guitar marketing. Imported guitar products with low prices and good quality have been proven to attract people's enthusiasm, so that local guitar products such as those marketed by Selekta Galaktika Musik are difficult to compete. Marketing efforts using social media have also been carried out, but have no significant impact on guitar product sales. Therefore, other efforts are needed to support digital marketing that has been carried out, namely by utilizing e-commerce in the form of a website. It is hoped that this website will be able to support promotional activities and can educate the public to choose local guitar products.